Improving the quality of publications in and advancing the paradigms of clinical and social pharmacy practice research: The Granada statements - Fernando Fernandez-Llimos; Shane Desselle; Derek Stewart; Victoria Garcia-Cardenas; Zaheer-; Christine Bond; Ana Dago; Ramune Jacobsen; Lotte Stig Nørgaard; Carlo Polidori; Manuel Sanchez-Polo; Bernardo Santos-Ramos; et al. (Taylor & Francis Group, 2023)
Abstract Pharmacy and pharmaceutical sciences embrace a series of different disciplines. Pharmacy practice has been defined as "the scientific discipline that studies the different aspects of the practice of pharmacy and its impact on health care systems, medicine use, and patient care". Thus, pharmacy practice studies embrace both clinical pharmacy and social pharmacy elements. Like any other scientific discipline, clinical and social pharmacy practice disseminates research findings using scientific journals. Clinical pharmacy and social pharmacy journal editors have a role in promoting the discipline by enhancing the quality of the articles published. As has occurred in other health care areas (i.e., medicine and nursing), a group of clinical and social pharmacy practice journal editors gathered in Granada, Spain to discuss how journals could contribute to strengthening pharmacy practice as a discipline. The result of that meeting was compiled in these Granada Statements, which comprise 18 recommendations gathered into six topics: the appropriate use of terminology, impactful abstracts, the required peer reviews, journal scattering, more effective and wiser use of journal and article performance metrics, and authors' selection of the most appropriate pharmacy practice journal to submit their work.